2020
DOI: 10.1101/2020.10.16.342956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The discovery, distribution and diversity of DNA viruses associated withDrosophila melanogasterin Europe

Abstract: Drosophila melanogaster is an important model for antiviral immunity in arthropods, but very few DNA viruses have been described in association with the Drosophilidae. This has limited the opportunity to use natural host-pathogen combinations in experimental studies, and may have biased our understanding of the Drosophila virome. Here we describe fourteen DNA viruses detectable by metagenomic analysis of 6.5 thousand pool-sequenced Drosophila, sampled from 47 European locations between 2014 and 2016. These inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 132 publications
(300 reference statements)
0
9
0
Order By: Relevance
“…A partial poxvirus genome sequence identified within the argentine ant, named Linepithema humile entomopoxvirus 1 (LHEV), represents the first hymenopteran (ant, wasp, and bee) poxvirus to be sequenced [ 43 ]. In addition, a complete poxvirus genome obtained from Drosophila melanogaster , known as Yalta virus, represents the first sequenced dipteran (fly) poxvirus [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A partial poxvirus genome sequence identified within the argentine ant, named Linepithema humile entomopoxvirus 1 (LHEV), represents the first hymenopteran (ant, wasp, and bee) poxvirus to be sequenced [ 43 ]. In addition, a complete poxvirus genome obtained from Drosophila melanogaster , known as Yalta virus, represents the first sequenced dipteran (fly) poxvirus [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The placement of the 7 originally sequenced EPVs (MSEV, AMEV, AHEV, MySEV, CREV, CBEV, and ACEV) on the tree shows concordance with the higher phylogenetic relationships of their insect hosts, which is consistent with previous EPV phylogenetic analyses [ 37 , 40 ]. In contrast, LHEV and Yalta virus show a clear divergence from other EPVs [ 44 ]. The inclusion of DlEPV in our phylogeny revealed that it shares a more recent common ancestor with Yalta virus than LHEV, suggesting that DlEPV is more likely derived from a fly pathogen rather than a parasitoid pathogen ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences were re-aligned in the proximity of insertions-deletions (indels) with GATK (v3.4-46; McKenna et al 2010). We identified and removed any reads that mapped to the D. simulans genome using a custom python script, following methods outlined previously (Machado et al 2019; Kapun et al 2020; for a more in-depth analysis of D. simulans contamination see Wallace et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences were re-aligned in the proximity of insertions-deletions (indels) with GATK (v3.4-46;McKenna et al 2010). We identified and removed any reads that mapped to the D. simulans genome using a custom python script, following methods outlined previously (Kapun et al 2020;Machado et al 2021; for a more in-depth analysis of D. simulans contamination see Wallace et al 2021). Although this method of decontamination by D. simulans accurately estimates contamination rate and removes the vast majority of D. simulans reads (Machado et al 2021), care should be taken when analyzing samples with higher contamination rates at sites that are shared polymorphisms between the two species.…”
Section: Sample Collectionmentioning
confidence: 99%